Treatment pattern by hormone receptors and HER2 status in patients with metastatic breast cancer in the UK, Germany, France, Spain and Italy (EU-5): results from a physician survey. (September 2012) - DeKoven, Mitch; Bonthapally, Vijayveer; Jiao, Xiaolong; Ganguli, Arijit; Pathak, Prathamesh; Lee, Won Chan; Ray, Saurabh
Background: The differences in country-specific treatment patterns across Europe for metastatic breast cancer (mBC) patients have not been extensively studied. This study compared the treatment choices in aggregate, as well as by biomarker status, between various lines of therapy in clinical practice in the EU-5 countries among newly diagnosed mBC patients.Materials & methods: The IMS LifeLink™ Oncology Analyzer database, based on surveys of practicing oncologists, was used to identify mBC patients aged ≥21 years. In this database, sample-level data are projected to national-level estimates for each country using a sample projection technique.Results: The prevalence of hormone receptors (71–74%) is quite similar across different countries, while HER2 overexpression varies from 22 (France) to 34% (Italy); chemotherapy combined with HER2-targeted medicine was the mainstay of treatment for HER2 + patients. The use of HER2-targeted medicine and bevacizumab greatly varied: while they were most frequently used in France, they were least frequently used in the UK. Fewer treatment options existed for triple-negative patients and patients with HER2 + disease following trastuzumab treatment. Chemotherapy was the treatment choice for triple-negative patients, as these patients do not respond to hormonal therapy and HER2-targeted medicine.Conclusion: This study found that, while a trastuzumab-based regimen is the preferred option for treating HER2 + mBC patients in the EU-5, variations in this personalized medicine approach exist between different EU-5 countries. However, fewer treatment options exist for triple-negative and HER2 + patients after trastuzumab treatment, highlighting the unmet need for these patient subgroups.